FEATURES OF INFORMATION SECURITY TRAINING BASED ON THE USE OF DIGITAL TECHNOLOGIES - Madyarova, Г.А.; Sattar, П.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The expansion of the scope of digital technologies in all spheres of society, the rapid increase in information flows causes an "information tsunami". This affects the increase in the susceptibility of personal data, documentary information and personal information to cyber attacks, and in this regard, the continuous improvement of information security knowledge is one of the topical issues of today. In order to ensure the safety of digital personal information belonging to each individual, it is necessary to provide him with systematic and reliable information about information security, starting from school age. In this article, the problems of forming students' knowledge of information security in a secondary school were considered. An expert analysis of the content and volume of textbooks on information security from three publishers (Arman PV, Almatykitap, Atamura) recommended by the Ministry of Education and Science revealed a number of problems, such as a variety of terms, topics covered and task levels. Taking into account the identified problems, an optional lesson model was developed for teaching information security in secondary school and the content of digital educational content was created.